VIDIIA Hunter : a low-cost, smartphone connected, artificial intelligence-assisted COVID-19 rapid diagnostic platform approved for medical use in the UK - Aurore, C.P.; Riaño Moreno, R.D.; Takaindisa, L.; Jessie, C.; Mehat, J.W.; Abi, H.; Rohaim, M.A.; Williams, C.; Burkhart, P.; Conlon, C.; Wilson, M.; McClumpha, M.; et al. (Frontiers in Molecular Biosciences, 2023)
Accurate and rapid diagnostics paired with effective tracking and tracingsystemsarekeytohaltingthespreadofinfectiousdiseases,limiting the emergenceofnewvariantsandtomonitorvaccineefficacy.Thecurrentgold standard test (RT-qPCR)forCOVID-19ishighlyaccurateandsensitive,butistimeconsuming,andrequiresexpensivespecialised,lab-basedequipment.
Keywords: Rapid diagnostics; LAMP(loop mediated isothermal amplification); COVID-19; Artificial intelligence; Infectious diseases